Documentation of growth and insulin-like growth factor I in Atlantic salmon (Salmo salar) post-smolts reared in large scale semi-closed and open systems - Gamlem, Ingrid (The University of Bergen, 2017)
Understanding the variation of growth performance in different large scale production scenarios is of great importance to the aquaculture industry to develop efficient rearing procedures for cultured fish. This study investigated the growth performance of Atlantic salmon (Salmo salar) post-smolts reared in the semi-closed system, Preline, compared to post-smolts reared in a traditional open cage. The study consisted of three different parts: (1) Freshwater period, (2) post-smolt period (Preline vs control systems), and (3) adult period in open cages. Smolts with the same biological and genetic background were divided into two groups, and reared in separate systems during the post-smolt period. Temperature and salinity differed between systems since the Preline system accessed water from a depth of 35 m. Control fish showed a higher growth rate compared to Preline fish during the post-smolt period. After two and four months, they also showed a significantly higher weight, length and condition factor compared to Preline fish, which was associated with higher temperature. The insulin-like growth factor I (IGF-I) plasma concentration was higher in control fish after one and two months, which was also associated with higher temperatures. However, no differences in plasma IGF-I concentration were found between systems after four months. Preline fish showed a higher growth rate compared to control fish when transferred to an open cage during the adult period, suggesting that they may have experienced a training affect during the post-smolt period from the constant water flow in the Preline semi-closed system. A higher expression of IGF-I binding proteins (IGFIBP) mRNA expression in muscle was seen in control fish at the end of the post-smolt period, which may have inhibited growth during the adult period. Masteroppgave i biologi BIO399